2016
DOI: 10.1126/science.aad9642
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia as a therapy for mitochondrial disease

Abstract: Defects in the mitochondrial respiratory chain (RC) underlie a spectrum of human conditions, ranging from devastating inborn errors of metabolism to aging. We performed a genome-wide, Cas9-mediated screen to identify factors that are protective during RC inhibition. Our results highlight the hypoxia response, an endogenous program evolved to adapt to limiting oxygen availability. Genetic or small molecule activation of the hypoxia response is protective against mitochondrial toxicity in cultured cells and zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
373
3
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(396 citation statements)
references
References 45 publications
18
373
3
2
Order By: Relevance
“…On the other hand, several studies have demonstrated a beneficial effect of reduced mitochondrial activity. For example, in a recent study, the cellular hypoxia response was activated in cell lines, in zebrafish, and in mice via pharmacological and genetic manipulations or via exposure to low oxygen levels (33). The hypoxia response caused a shift to glycolytic energy metabolism and provided neuroprotection in a mouse model of Leigh syndrome, a genetic defect of respiratory chain function.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have demonstrated a beneficial effect of reduced mitochondrial activity. For example, in a recent study, the cellular hypoxia response was activated in cell lines, in zebrafish, and in mice via pharmacological and genetic manipulations or via exposure to low oxygen levels (33). The hypoxia response caused a shift to glycolytic energy metabolism and provided neuroprotection in a mouse model of Leigh syndrome, a genetic defect of respiratory chain function.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic or small-molecule activation of the hypoxia response is, therefore, protective against mitochondrial toxicity (150).…”
Section: Perspectivesmentioning
confidence: 99%
“…Although our ability to obtain a genetic diagnosis has vastly improved (see below), there remains little in the way of effective treatment. Several treatment approaches have been successful in animal models (11,23,46,47,104), but there is little evidence that this has progressed to effective clinical trials in humans. The lack of effective treatment highlights the importance of developing methods to prevent transmission of mitochondrial disease.…”
Section: Mitochondrial Diseasementioning
confidence: 99%